Агроекологічна оцінка садопридатності рекультивованих земель Нікопольського марганцеворудного родовища - Харитонов, Микола Миколайович; Kharytonov, Mykola; Чабан, І.П.; Chaban, І. (Уманський національний університет садівництва, 2016)
Стаття присвячена питанню садопридатності та екотоксикологічній оцінці застосування рекультивованих земель Нікопольского марганцеворудного родовища для отримання екологічно безпечних плодів яблуні. У процесі тривалого вивчення у стаціонарних дослідах різних заходів передпосадкової підготовки та варіантів відсипки було закладено декілька модельних варіантів рекультивованих земель. У досліджуваних варіантах передбачалась посадка дерев без локального і з локальним внесенням чорнозему. Локальне внесення чорноземної маси перед посадкою дерев сприяє створенню багаторічних насаджень з продуктивністю на рівні зональних ґрунтів. При вирощуванні яблуні сорту Кальвіль сніговий на рекультивованих землях Нікопольського МРБ тривалість вікових періодів становила: період росту і плодоношення - 3 роки; плодоношення - 6 років; плодоношення та відмирання - 9 років; відмирання, плодоношення і відновлення - 7 років; відмирання, ріст і плодоношення - 18 років. Вміст марганцю в солянокислой витяжці за профілем лесоподібного суглинку коливався був в 2-4 рази менше, порівняно з даними по чорнозему південому. Розподіл решти важких металів за профілем - практично однаковий. Порівняльний аналіз даних засвідчив, що вміст важких металів у яблуках не перевищує норм ГДК.The article is devoted to the question of suitability for apple orchards management and ecotoxicological assessment of use of reclaimed lands of the Nikopol manganese ore deposit to obtain environmentally friendly fruit. The main experimental work was carried out in multi-year field experiment with apple variety Winter Calville grafted on dwarf M9 rootstock. In the course of a long study in stationary experiments of different ways of pre-training and variants of spread a few model variants, of reclaimed mine lands were laid. In the test options provided for the planting of trees without the local and with local application of topsoil. Local application of black mass before planting trees promotes the establishment of long-term Plantations with productivity at the level of zonal soils. The duration of age periods included: the period of growth and fruiting - 3 years; fruition - 6 years; the fruiting and withering - 9 years old; the drying, fruiting and growth - 7 years; the shrinking, the growth and fruiting-18 years. The average yield of apple in the first three periods ranged from 76.8 per (loess-like sediments) to 91.0 kg/ha (local application of black earth masses) and was close to the productivity on zonal soils, and fruits with shelf life and visual appeal had a certain advantage. Pre-filling of pits and trenches loess-like sediments have a deterrent effect on the size of the trees. High performance of apple trees was observed during two decades, and then plummeted. The manganese content in the 1N HCl extract on the profile of loess-like loam ranged 2-4 times less in comparison with the data on the southern black soil. The distribution of the remaining heavy metals in the profile is practically identical. Comparative data analysis showed that the content of heavy metals in apples does not exceed norms of maximum permissible concentration.
AGROECOLOGICAL ASSESSMENT OF RECLAIMED MINELANDS OF NIKOPOL MANGANESE ORE DEPOSIT FOR ORCHARDS SUITABILITY
Keywords: яблука; apples; сад; orchard; рекультивовані землі; reclaimed minelands; придатність; suitability; екологічна безпека; environment safety; важкі метали; heavy metals